ANTI-INFLAMMATORY AND ANALGESIC ACTIVITIES OF AVOCADO SEED (Persea americana Mill.) - Caecilia Desi Kristanti; Fransisca Puspa Jelita Simanjuntak; Ni Kadek Pramita Anggara Dewi; Skolastika Venita Tianri; Phebe Hendra (Sanata Dharma University, 2017)
The purpose of this research is to evaluate the anti-inflammatory and analgesic activities of infusion and methanolic extract from avocado seeds. The anti-inflammatory activity was determined using carrageenan-induced paw edema in mice. The analgesic activity was assessed using acetic acid stimuli to induce peripheral pain in mice. Results of this research showed that both all level doses of infusion and methanolic extract of avocado seeds have a significant reduction on the mice paw edema. All level doses of methanolic extract of avocado seeds have a significant reduction on the number of abdominal writhes induced by acetic acid, but only the lowest dose of infusion showed a significant reduction. Our findings suggest that avocado seeds contains potential anti-inflammatory and analgesic compounds which support its traditional use. Further phytochemical studies are required to determine the active compounds are actually responsible for such properties.